Каріологія європейських видів роду Gentiana L. (Gentianaceae) - Страшнюк, Н.М.; Твардовська, М.О.; Мельник, В.М (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Обобщены литературные данные о хромосомных числах европейских видов рода Gentiana, представлены собственные результаты их цитогенетических исследований из разных локалитетов в Украине. Сравнение результатов собственных кариологических исследований с литературными данными подтверждает полученные ранее хромосомные числа видов G. lutea, G. punctata, G. acaulis, G. verna, G. cruciata, G. pneumonanthe, а также одной из цитологических рас G. asclepiadea. Рассмотрены кариологические особенности секций и отдельных представителей рода в связи с их распространением. Обсуждается необходимость дальнейших кариологических исследований для выяснения эволюции видов рода Gentiana и классификации его отдельных таксонов. The work summarizes the literature data on chromosome numbers of European species of Gentiana and our original results concerning their cytogenetics from various localities in Ukraine. Based on the comparison of the results of our own studies with those of literature, there were confirmed previously reported chromosome numbers in G.lutea, G.punctata, G.acaulis, G.verna, G.cruciata and G.pneumonanthe, as well as those of one race of G.asclepiadea. Karyological details for some sections and individual members of the genus in context of their propagation were considered. The necessity for further karyological investigations to elucidate Gentiana species evolution and taxonomy was discussed.